Grouper Interferon-Induced Transmembrane Protein 1 Inhibits Iridovirus and Nodavirus Replication by Regulating Virus Entry and Host Lipid Metabolism - Zhang, Ya; Wang, Liqun; Zheng, Jiaying; Huang, Liwei; Wang, Shaowen; Huang, Xiaohong; Qin, Qiwei; Huang, Youhua (Frontiers in Immunology, 2021)
Interferon-induced transmembrane proteins (IFITMs) are novel viral restriction factors which inhibit numerous virus infections by impeding viral entry into target cells. To investigate the role of IFITMs during fish virus infection, we cloned and characterized an IFITM1 homolog from orange spotted grouper (Epinephelus coioides) (EcIFITM1) in this study. EcIFITM1 encodes a 131-amino-acid polypeptide, which shares a 64% and 43% identity with Seriola dumerili and Homo sapiens, respectively. The multiple sequence alignment showed that EcIFITM1 contained five domains, including NTD (aa 145), IMD (aa 4667), CIL (aa 6893), TMD (aa 94119), and CTD (aa 120131). In vitro, the level of EcIFITM1 mRNA expression was significantly up-regulated in response to Singapore grouper iridovirus (SGIV), or red-spotted grouper nervous necrosis virus (RGNNV) infection. EcIFITM1 was primarily distributed in the cytoplasm and colocalized with early endosomes, late endosomes, and lysosomes to varying degrees. The ectopic expression of EcIFITM1 significantly inhibited the replication of SGIV or RGNNV, which was reflected in decreased virus production, as well as the level of viral gene transcription and protein expression. In contrast, a knockdown of EcIFITM1 using small interfering RNAs (siRNAs) promoted the replication of both viruses. Both EcIFITM1 overexpression and knockdown suggested that EcIFITM1 suppressed viral entry into host cells. Furthermore, the results of non-targeted lipometabolomics showed that EcIFITM1 overexpression could induce lipid metabolism remodeling in vitro. Importantly, all of the detected ceramides were significantly increased following EcIFITM1 overexpression, suggesting that EcIFITM1 may suppress SGIV entry by regulating the level of ceramide in the lysosomal system. Additionally, EcIFITM1 overexpression positively regulated both interferon-related molecules and ceramide synthesis-related genes. Taken together, our results demonstrated that EcIFITM1 exerted a bi-functional role, including immune regulation and lipid metabolism, in the context of fish virus infections.